2022
DOI: 10.1007/s00424-022-02720-9
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin does not prevent development of hypoxia-induced pulmonary edema in rats

Abstract: Acute hypoxia impairs left ventricular (LV) inotropic function and induces development of pulmonary edema (PE). Enhanced and uneven hypoxic pulmonary vasoconstriction is an important pathogenic factor of hypoxic PE. We hypothesized that the potent vasodilator relaxin might reduce hypoxic pulmonary vasoconstriction and prevent PE formation. Furthermore, as relaxin has shown beneficial effects in acute heart failure, we expected that relaxin might also improve LV inotropic function in hypoxia. Forty-two rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(111 reference statements)
0
0
0
Order By: Relevance
“…TNF is a potent stimulator of inflammatory responses in many pulmonary diseases such as asthma, chronic obstructive pulmonary disease (COPD), acute lung injury/acute respiratory distress syndrome (ALI/ARDS) but also HAPE and high-altitude pulmonary hypertension (HAPH) [49,50]. In previous studies, we also found increased levels of TNF in the lungs of rats exposed to normobaric hypoxia with an oxygen content of 10% over time intervals between 6 and 24 h [13,28]. The present results show that TNF is still highly expressed after 72 h of hypoxia suggesting that inflammatory processes are still active and can maintain edema formation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…TNF is a potent stimulator of inflammatory responses in many pulmonary diseases such as asthma, chronic obstructive pulmonary disease (COPD), acute lung injury/acute respiratory distress syndrome (ALI/ARDS) but also HAPE and high-altitude pulmonary hypertension (HAPH) [49,50]. In previous studies, we also found increased levels of TNF in the lungs of rats exposed to normobaric hypoxia with an oxygen content of 10% over time intervals between 6 and 24 h [13,28]. The present results show that TNF is still highly expressed after 72 h of hypoxia suggesting that inflammatory processes are still active and can maintain edema formation.…”
Section: Discussionmentioning
confidence: 86%
“…Isolated -AB had weaker effects on LV function, but reduced TPR indicating a vasodilatory effect. Vasodilation in the pulmonary vasculature in combination with a reduced LV relaxation and slightly elevated LV edP suggest increased congestion in the pulmonary vascular bed [28]. These alterations of cardiovascular functions by adrenergic blockers and the resulting backlog into the lungs may explain the aggravation of PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation